MANAGEMENT OF GERONTIC NURSING CARE WITH SERVICE EXCELLENT FOR MR. J WITH ATOPIC DERMATITIS AT THE BINJAI SOCIAL SERVICES FOR THE ELDERLY DEPARTEMENT OF SOCIAL SERVICES NORTH SUMATRA PROVINCE IN 2025 - Siburian, Lilis NR; Rosmega; Ella Riania Manurung; Ribka Hutajulu; Eriska Br Munte; Fidhelia Anastasya Br Barus; Zulkarnain Batubara, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Atopic dermatitis is a chronic inflammatory skin condition that commonly affects elderly individuals due to age-related immune decline and suboptimal personal hygiene practices. This condition not only causes significant discomfort but can also lead to complications that impact the quality of life in older adults. In the Binjai Elderly Social Service Unit (UPTD), North Sumatra, 8 out of 198 residents (4.04%) were reported to have symptoms consistent with atopic dermatitis. Among these, Mr. J, a 65-year-old resident, presented with notable clinical features such as persistent itching, skin lesions due to scratching, dry skin, and disturbed sleep patterns. To address this issue, a comprehensive geriatric nursing care management plan was implemented using a service excellent approach, aimed at improving patient comfort and promoting effective self-care. The study employed a descriptive case study method conducted from March to April 2025, using direct interviews, observations, physical examinations, and documentation to gather data. Through the nursing process—assessment, diagnosis, planning, implementation, and evaluation—the nursing team identified three primary problems: impaired skin integrity, discomfort due to itching, and a deficit in self-care. Interventions included the use of emollients, administration of topical hydrocortisone cream, education on personal hygiene, and strategies to encourage patient motivation and independence in daily care. The outcomes demonstrated a marked improvement in skin condition, reduction in itching, improved sleep quality, and increased awareness and participation in personal hygiene practices. This case study highlights the critical role of nurses in delivering holistic, patient-centered care to elderly individuals suffering from atopic dermatitis. A service excellent approach, grounded in empathy, education, and evidence-based interventions, proves to be a powerful model in managing chronic skin conditions in geriatric settings.